Wprowadzenie do outsourcingu w zakładach opieki zdrowotnej - Nieplowicz, Maria (The Introduction to the Outsourcing in Health Care Units, 2009)
The target of the paper is to show the essence of health care unit, describe outsourcing's methods and show the possibility of using outsourcing in health care unit. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 75-81